2022
DOI: 10.1111/jgh.15902
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gastro‐esophageal reflux symptoms on the risk of Barrett's esophagus: A systematic review and meta‐analysis

Abstract: Background and Aim Gastro‐esophageal reflux (GER) is the main predisposing factor for Barrett's esophagus (BE). A more precise estimate of the association of GER symptoms with the risk of BE would be important to prioritize endoscopic screening. We conducted a systematic review and meta‐analysis to examine this issue. Methods MEDLINE, EMBASE, and EMBASE Classic were searched to identify cross‐sectional studies that reported the prevalence of BE based on presence of GER symptoms. The prevalence of BE was compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…The relationship between GERD and chronic cholecystitis is intricate, involving complex mechanisms. Research has demonstrated that patients with esophagitis and Barrett's esophagus exhibit substantially elevated levels of bile acids compared to control groups, which are linked to acid re ux (31,32), and bile re ux-induced chemical damage has been identi ed as a signi cant contributor to esophageal mucosal rupture and refractory GERD in patients. Abnormal gallbladder function and anatomical structure are known to be contributing factors to cholestasis, which can result in impaired gallbladder function in terms of bile concentration and biliary pressure regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between GERD and chronic cholecystitis is intricate, involving complex mechanisms. Research has demonstrated that patients with esophagitis and Barrett's esophagus exhibit substantially elevated levels of bile acids compared to control groups, which are linked to acid re ux (31,32), and bile re ux-induced chemical damage has been identi ed as a signi cant contributor to esophageal mucosal rupture and refractory GERD in patients. Abnormal gallbladder function and anatomical structure are known to be contributing factors to cholestasis, which can result in impaired gallbladder function in terms of bile concentration and biliary pressure regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, early EC cases could be missed for various reasons. Diagnosis of EC is difficult as systems could be nonspecific Gastrointestinal reflux Disease-(GERD-) like symptoms [27]. First, remote areas of Tanzania may not be served by a regional hospital that can provide diagnostic laboratory services and radiology, compared to ORCI, which provides these services and can aid in detecting EC [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy is also recommended in all patients with GERD symptoms and at least 2 of the following risks factors for Barrett’s esophagus: Age ≥ 50 years, male gender, Caucasian ethnicity, obesity, family history for Barrett’s esophagus or esophageal adenocarcinoma, and smoking[ 2 , 5 ]. Indeed, the prevalence of Barrett’s esophagus among patients with GERD symptoms is only about 5%-7%[ 6 , 7 ], therefore endoscopy should be reserved to patients with multiple risk factors for this condition.…”
Section: Question 1: Should I Perform Endoscopy In All Patients With ...mentioning
confidence: 99%